The discovery of 2-hydroxymethyl-3-(3-methylbutyl)-5-methylpyrazine: A semiochemical in orchid pollination - Bohman, B.; Jeffares, L.; Flematti, G.; Phillips, R.; Dixon, Kingsley; Peakall, R.; Barrow, R. (2012)
Drakaea livida (Orchidaceae) is pollinated by sexual deception of the wasp Zaspilothynnus nigripes (Thynnidae). It is shown that the orchid emits the same compound, 2-hydroxymethyl-3-(3-methylbutyl)-5-methylpyrazine, that females emit when calling for mates. This novel pyrazine was isolated and identified by GC-EAD and GC-MS and confirmed by synthesis. This compound may represent the first known case of pyrazines as sex pheromones in Hymenoptera.